2017
DOI: 10.1021/acs.energyfuels.6b02645
|View full text |Cite
|
Sign up to set email alerts
|

Pyrolysis Two-Dimensional GC-MS of Miscanthus Biomass: Quantitative Measurement Using an Internal Standard Method

Abstract: Accurate measurement of biomass pyrolysis products can provide valuable guidance for thermal processing. However, pyrolysis generates large numbers of compounds in varying concentrations, factors that can make compound identification and quantitation difficult. In this study, Miscanthus biomass samples were analyzed using pyrolysis/two-dimensional gas chromatography/mass spectrometry (Py-GCxGC-MS), which provided a more comprehensive chromatographic separation and mass spectral compound identification. Quantit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 72 publications
1
24
2
Order By: Relevance
“…S‐lignol decomposition products were very less compared to those from H and G‐lignols even at higher temperatures (550°C). Groenewold et al reported 10.37 wt.% as the highest yield of LVG, 1.44 wt.% of acetic acid, 0.19 wt.% furfural, 0.13 wt.% of 5‐HMF (Groenewold et al, ). The results of furfural (0.24 %) and 5‐HMF (0.22 %) are comparable to those of Negahdar et al, while LVG and acetic acid were reported as 5.6% and 4.6%, respectively (Negahdar et al, ).…”
Section: Mechanistic and Intrinsic Kinetic Studies Of Biomass Pyrolysismentioning
confidence: 99%
See 2 more Smart Citations
“…S‐lignol decomposition products were very less compared to those from H and G‐lignols even at higher temperatures (550°C). Groenewold et al reported 10.37 wt.% as the highest yield of LVG, 1.44 wt.% of acetic acid, 0.19 wt.% furfural, 0.13 wt.% of 5‐HMF (Groenewold et al, ). The results of furfural (0.24 %) and 5‐HMF (0.22 %) are comparable to those of Negahdar et al, while LVG and acetic acid were reported as 5.6% and 4.6%, respectively (Negahdar et al, ).…”
Section: Mechanistic and Intrinsic Kinetic Studies Of Biomass Pyrolysismentioning
confidence: 99%
“…More such experiments are needed to investigate the intrinsic kinetics of biomass fast pyrolysis. Recently, Groenewold et al (2017) have demonstrated quantitative analysis of biomass fast pyrolysis products in a Py-GCxGC-MS system with 9-(9H)-fluorenone vapors introduced as internal standard at the interface of reactor and injector of the GC. Because the variation of mono-lignol release with respect to temperature could be well captured one could conclude that the H-lignol decomposition products were most abundant at low temperatures (400 C), while G-lignol products were abundant at 450 C. S-lignol decomposition products were very less compared to those from H and G-lignols even at higher temperatures (550 C).…”
Section: Biomassmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, there are approximately 17 species investigated in Europe for energy and material development including Miscanthus tinctorius, M. sinensis, M. sacchariflorus and the triploid genotype M. x giganteus, an allotriploid hybrid of the diploid M. sinensis and the tetraploid M. sacchariflorus. Miscanthus field trials have been performed in Europe over the past 25 years and their linkages differ significantly [49][50][51][52][53][54][55][56][57][58][59][60]. Figure 1 shows the most common linkages of lignin formed during biosynthesis, some of them confirmed within the last five years [55,61,62].…”
Section: Introductionmentioning
confidence: 99%
“…At a high mass resolving power, the data acquisition rate and mass accuracy were not significantly impacted by changing the IT from 1 to 5 milliseconds and the value of the AGC target from 10 5 to 10 6 (Table 1). However, at the lowest mass resolving power (7500), the data acquisition rate decreased from 43 to 36 Hz, whereas the IT increased from 1 to 5 milliseconds (the AGC target was set as 10 6 ). It could be noticed that the absolute intensities and S/N remained steady while the parameters changed, demonstrating that the resolving power did not affect the sensitivity of the results.…”
Section: Resultsmentioning
confidence: 99%